2012
DOI: 10.31436/iiumej.v13i2.289
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Parametric Analyses on Effect of Fibre Orientation for Stress Concentration Factor in Fibrous Composite Cantilever Plate with Central Circular Hole under Transverse Loading

Abstract: A number of analytical and numerical techniques are available for the two dimensional study of stress concentration around the hole(s) in isotropic and composite plates subjected to in-plane or transverse loading conditions. The information on the techniques for three dimensional analyses of stress concentration factor (SCF) around the hole in isotropic and composite plates subjected to transverse loading conditions is, however, limited. The present work emphasizes on the effect of fibre orientation (q) on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Several studies were reported [34][35][36][37][38] predicting the fatigue life theoretically or by comparing with experimental results. ANSYS was used [39,40] in predicting the stress concentration areas. However, the design of the 3D model was by different computer aided design (CAD) software before being imported to the desired numerical software to run the fatigue analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were reported [34][35][36][37][38] predicting the fatigue life theoretically or by comparing with experimental results. ANSYS was used [39,40] in predicting the stress concentration areas. However, the design of the 3D model was by different computer aided design (CAD) software before being imported to the desired numerical software to run the fatigue analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Ghezzo et al [5] performed a numerical and experimental analysis of the interaction between two notches in carbon fibre laminates. Jain and Mittal [6] analyzed the effect of fibre orientation on stress concentration factor in fibrous plate with central circular hole under transverse static loading by using two dimension finite element methods. The numerical analysis of the stress distribution in-plane -stress assumption and within the fibrous plate theory framework has been conducted on two symmetric laminates.…”
Section: Introductionmentioning
confidence: 99%
“…Jain and Mittal[17] have analyzed the stress concentration and deflection in isotropic, orthotropic and laminated composite plates with central circular hole subjected to transverse static loading by using two dimensional fmite element methods. Mittal and Jain[18] analyzed the effect of fibre orientation on stress concentration factor in fibrous plate with central circular hole under transverse static loading by using two dimension finite element methods. Ghezzo et al[19] performed a numerical and experimental analysis of the interaction between two notches in carbon fibre laminates.…”
mentioning
confidence: 99%